Multiscale Characterisation of Environmentally Assisted Cracking in Al-Zn-Mg-Cu Aluminium Alloys - V. Landais; J. Robson; J. Carr; J. Fellowes (Canadian Institute of Mining, Metallurgy and Petroleum, 2018)
"Aerospace Al-Zn-Mg-Cu (7xxx) alloys are known to be susceptible to environmentally assisted cracking (EAC). This phenomenon has been studied intensively for many decades, leading to empirically adopted methods to mitigate this problem through overaging and composition design. In parallel, many theories have been developed to explain EAC in 7xxx, but none is yet universally accepted. Today, a number of emerging techniques offer potential to shed new light on EAC in 7xxx. The purpose of the present paper is to demonstrate how X-ray tomography (XCT) combined with electron microscopy can be used to identify the true crack path in 3-dimensions, and hence identify material for site specific electron microscopy analysis. Composition mapping over large areas to high accuracy has been performed using a modern electron microprobe analysis system. This has been combined with transmission electron microscopy to investigate local composition in matrix and precipitates at high resolution. This combination of techniques across length scales offers the potential to provide new insights into the links between local composition, microstructure, and EAC resistance.INTRODUCTION Environmentally-assisted cracking (EAC) is a phenomenon which dramatically decreases the performance of metals and can cause premature failure of large structures. Observed in situations where components were not subjected to critical loads and no widespread corrosion was involved, this type of brittle failure is extremely difficult to predict. The EAC designation covers a number of phenomena, e.g. stress corrosion cracking (SCC), hydrogen embrittlement (HE), corrosion fatigue (CF), etc. Initially identified in steels, EAC can also affect other metals such as high-performance aerospace aluminium alloys, and this phenomenon has been a concern for industries for decades. Extensive research has been conducted on the effects of various environments (moist air, saline water, dry hydrogen gas, etc.) on microstructures and crack propagation, however no consensus has been reached and the exact nature of the mechanisms that control EAC is still being debated (Birnbaum & Sofronis, 1994; Gangloff, 2007; Holroyd & Scamans, 2013; Lynch, 2012; Oriani, 1972; Scamans, Alani & Swann, 1976, Young & Scully, 2002)."